2012
DOI: 10.1038/nri3209
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent mesenchymal stromal cells and the innate immune system

Abstract: Multipotent mesenchymal stromal cells (MSCs) have unique immunoregulatory and regenerative properties that make them an attractive tool for the cellular treatment of autoimmunity and inflammation. Their underlying molecular mechanisms of action together with their clinical benefit - for example, in autoimmunity - are being revealed by an increasing number of clinical trials and preclinical studies of MSCs. However, autoimmunity and therapy-related alloimmunity are not only triggered and sustained by responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
738
0
16

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 863 publications
(770 citation statements)
references
References 137 publications
16
738
0
16
Order By: Relevance
“…[41][42][43][44][45] In this section, we will briefly discuss some of these properties, which are summarized in Table 2.…”
Section: Immune Modulation By Mscsmentioning
confidence: 99%
“…[41][42][43][44][45] In this section, we will briefly discuss some of these properties, which are summarized in Table 2.…”
Section: Immune Modulation By Mscsmentioning
confidence: 99%
“…In contrast, MSCs can promote the differentiation to M2 macrophages which abundantly produce IL-10 [13]. These modulations of immune cells are associated with many soluble factors released from MSCs, including transforming growth factor-β1, hepatocyte growth factor, IL-10, indoleamine 2, 3-dioxygenase, prostaglandin E2, nitric oxide, matrix metalloproteinases, HLA-G (Figure 1) [11][12][13][14]. The secretion of these factors from MSCs has been shown to be induced by IFN-γ alone, or in combination with tumor necrosis factor (TNF)-α, IL-1α, or IL-1β [23].…”
Section: Immunomodulatory Function Of Mscsmentioning
confidence: 97%
“…The immunomodulatory effect of MSCs was first indicated by long term engraftment in a xenogeneic environment in 2000 [10]. Although its mechanisms have not been fully understood, previous studies have revealed that MSCs inhibited the function of immune cells via cell to cell contact dependent mechanism and several soluble immune modulators [11][12][13][14].…”
Section: Immunomodulatory Function Of Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that MSCs are immunomodulatory and are capable of reducing pathogenic inflammation [31]. MSCs can exert profound immunosuppression both in vitro and in vivo by inhibiting the proliferation of T-cells, natural killer cells, and dendritic cells [32].…”
Section: Phenotype Of Mscsmentioning
confidence: 99%